Intermediaries as Innovating Actors in the Transition to a Sustainable Energy System - Julia Backhaus (Central European Journal of Public Policy, 2010)
In transitions of large sociotechnical systems, intermediary organisations can emerge as mediators in between several actor groups and facilitate communication and collaboration towards common goals. They can support the establishment of new actor networks and the articulation and alignment of interests to bring about desired changes. In this article, current efforts towards a more sustainable energy system serve as an exemplary context of intermediary work. The field under scrutiny, demand side management, aims to decrease energy consumption. Unfortunately, the role and work of intermediaries as implementers of demand side management projects often remains underappreciated. Research into the reasons of successes and failures of intermediary work and a theoretical corroboration for their practical work can help intermediaries to improve their programme designs and implementation strategies. The EC FP7-funded Changing Behaviour project aims to support intermediaries with strategic activities to improve demand side management programmes and bring about lasting behavioural changes. Paying more attention to context, stakeholders, monitoring, evaluation and learning enables the development of tailor-made, widely supported projects with higher chances of success. In addition to practical support for their work, intermediaries can benefit from stronger policy support. Understanding and appreciation of their work as contribution to policy implementation, e.g. towards energy saving targets, could motivate such support. A stable policy and financial environment with long-term implementation plans and funding schemes provides a fertile ground for intermediary activities. Active participation of policy actors in demand side management programmes can create networks sustaining longer-lasting change.